STUDENTSâ€™ PERCEPTIONS OF TEACHERSâ€™ WRITTEN CORRECTIVE FEEDBACK IN THE MALAYSIAN ESL CLASSROOM - Malini N. G. Ganapathy; Debbita Tan Ai Lin; Jonathan Phan (UUM Press, 2020)
Purpose â€" This study examined the types of written corrective feedback provided to ESL students in writing classes in Malaysian secondary schools, and their perceptions towards the provision of written corrective feedback in the Malaysian context.   Methodology â€" A survey questionnaire was administered randomly among 720 Form Four students from 10 secondary schools in Penang. The questionnaire was based on a Likert scale and responses were analysed using descriptive statistics.   Findings â€" Results showed that most learners benefited from and preferred direct feedback, and tended to focus on form such as grammar, paragraph organisation, content and clarity of ideas. Students preferred this form of feedback as they were able to understand errors more clearly. It was found that most students were unable to self-regulate their own errors; a majority could not locate their own errors and had become passive learners within the Malaysian schooling system.   Significance â€" The study is significant to Malaysian secondary schools in its effects, depicting the many forms of corrective feedback available in the ESL context that can be employed in school besides the popularized direct feedback used within the syllabus.